2023
DOI: 10.1097/cce.0000000000000863
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Intubation in COVID-19: When It Is Too Early and When It Is Too Late

Abstract: The timing of initiating mechanical ventilation in patients with acute respiratory distress syndrome due to COVID-19 remains controversial. At the outset of the pandemic, "very early" intubation was recommended in patients requiring oxygen flows above 6 L per minute but was followed closely thereafter by avoidance of invasive mechanical ventilation (IMV) due to a perceived (yet overestimated) risk of mortality after intubation. While the use of noninvasive methods of oxygen delivery, such as high-flow nasal ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, the question of the ideal timing for intubation remains unresolved [ 28 30 ]. To sum up, mortality appears to be higher when either a “very early” or a “very delayed” intubation strategy is used [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the question of the ideal timing for intubation remains unresolved [ 28 30 ]. To sum up, mortality appears to be higher when either a “very early” or a “very delayed” intubation strategy is used [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…One might consider this group of patients to have been in the very early intubation group of the Manrique study [24] that had poorer outcomes than their later counterparts. Taken together, the evidence points to an optimal period for intubation benefitting those patients whose respiratory insufficiency continues to go unresolved or show a negative trend [27].…”
Section: Timing Of Intubation In Covid-19 Pneumoniamentioning
confidence: 91%
“…In the early stages of the pandemic, it was recommended to intubate patients with COVID-19 very early when their oxygen requirements exceeded 6L/min, primarily as a measure to prevent the spread of the virus [ 1 , 2 ]. However, subsequent evidence regarding the potential benefits of high-flow nasal cannula (HFNC) oxygen therapy and non-invasive mechanical ventilation, coupled with concerns about the potential harm caused by premature unnecessary intubation, have raised questions regarding the very early intubation strategy [ 3 , 5 ]. Meanwhile, a meta-analysis including 20 non-randomized controlled studies revealed higher in-hospital mortality in patients that were intubated 24–48 hours or later after admission [ 8 ].…”
Section: Introductionmentioning
confidence: 99%